Kontribusi harga dan kepercayaan konsumen untuk membentuk kepuasan pengguna transportasi berbasis aplikasi - Efendi Efendi; Sri Harini (Journal of Business & Banking)
The rapid growth of internet usage has affected several sectors of human life, not least in the transportation sector. The implications of mobilizing the use of application-based transportation (GoJek) are now a trend among people to travel from one place to another. This condition illustrates that the intensity of the use of application-based transportation will have implications for the level of user satisfaction. The purpose of this study is to determine the contribution of price and consumer confidence to consumer satisfaction of users on the basis of application transportation. This research uses a case study model by involving students in one of the tertiary institutions in Pematang-siantar City. The number of samples in this study were 322 students obtained through non-probability sampling techniques with a purposive sampling method. Data collection uses an online questionnaire that is distributed to all samples in the form of a link (URL). Data analysis uses SEM test models consisting of measurement models and structural models. The results of research and hypothesis testing explain that price has a significant effect on user satisfaction of application-based applications. Furthermore, consumer confidence has a significant influence on user satisfaction based on application applications.